FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY - Dimas Wicaksono; Vera Sintia (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the effect of Audit Opinion, Solvability, and Company Size on Audit Delay in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2021 period. The population of this study includes all Property and Real Estate Sector companies Listed on the Indonesia Stock Exchange for the 2018-2021 period. Samples were taken using purposive sampling method with certain criteria, during the study period. The independent variables in this study are audit opinion which is measured using the dummy method in the related year, solvency which is measured by dividing total debt by total equity, and company size which is measured by multiplying LN by total assets. Meanwhile, the dependent variable in this study is Audit Delay, which is measured by subtracting the audit report date from the financial statement date or the book closing date. The results of this study indicate that: (1) Audit opinion has a negative effect on the occurrence of audit delay (2) Solvability has no effect on the occurrence of audit delay. (3) Firm size has no effect on audit delay.